NOX Activation by Subunit Interaction and Underlying Mechanisms in Disease - Rastogi, Radhika; Geng, Xiaokun; Li, Fengwu; Ding, Yuchuan (Frontiers in Cellular Neuroscience, 2017)
Nicotinamide adenine dinucleotide phosphate (NAPDH) oxidase (NOX) is an enzyme complex with the sole function of producing superoxide anion and reactive oxygen species (ROS) at the expense of NADPH. Vital to the immune system as well as cellular signaling, NOX is also involved in the pathologies of a wide variety of disease states. Particularly, it an integral player in many neurological diseases, including stroke, TBI, and neurodegenerative diseases. Pathologically, NOX produces an excessive amount of ROS that exceed the body’s antioxidant ability to neutralize them, leading to oxidative stress and aberrant signaling. This prevalence makes it an attractive therapeutic target and as such, NOX inhibitors have been studied and developed to counter NOX’s deleterious effects. However, recent studies of NOX have created a better understanding of the NOX complex. Comprised of independent cytosolic subunits, p47-phox, p67-phox, p40-phox, and Rac, and membrane subunits, gp91-phox and p22-phox, the NOX complex requires a unique activation process through subunit interaction. Of these subunits, p47-phox plays the most important role in activation, binding and translocating the cytosolic subunits to the membrane and anchoring to p22-phox to organize the complex for NOX activation and function. Moreover, these interactions, particularly that between p47-phox and p22-phox, are dependent on phosphorylation initiated by upstream processes involving PKC. This review will look at these interactions between subunits and with PKC. It will focus on the interaction involving p47-phox with p22-phox, key in bringing the cytosolic subunits to the membrane. Furthermore, the implication of these interactions as a target for NOX inhibitors such as apocynin will be discussed as a potential avenue for further investigation, in order to develop more specific NOX inhibitors based on the inhibition of NOX assembly and activation.